Nursing Implementation of Ineffective Breathing Patterns in Toddlers with Acute Respiratory Infection: A Case Study - Hamidah Retno; Leni Agustin; Saniyah Tabriz (KHD Production, 2024)
Acute Respiratory Infection is an upper and lower respiratory tract infection that attacks the throat, nose and lungs at mild to severe levels lasting approximately 14 days. This study uses a case study method in the form of a description of the nursing care process in patients in accordance with the theory and contains a discussion of nursing actions that occur in the field. This study was conducted for 3 days with a total of 3 visits to patients starting from 15-17 May 2023, data obtained from interviews, observations, physical examinations. This study uses the concept of nursing care starting from assessment, appointment of nursing diagnoses, provision of nursing interventions, nursing implementation and nursing evaluation carried out for 3 days. the instrument used is the surgical medical nursing care assessment format. The results obtained by Baby D that he was less congested after being given nebulizer therapy, pulse: 160x/min, Temperature: 36.70C, respiration rate: 55x/min, Spo2: 99%, baby D still looks a little tight, using a breathing apparatus (nasal cannula), the client's general condition has improved slightly. It is expected that clients and families maintain and improve health by implementing a healthy lifestyle and utilizing existing health facilities for health control to accelerate recovery, so that the problem of Ineffective Breathing Patterns in clients with Acute Respiratory Tract Infection can be resolved.